Improving pore-filling in TiO2 nanorods and nanotubes scaffolds for perovskite solar cells via methylamine gas healing. (August 2018) - Nawaz, Asmat; Wong, Ka Kan; Ebenhoch, Carola; Zimmermann, Eugen; Zheng, Zhaoke; Akram, Muhammad Nadeem; Kalb, Julian; Wang, Kaiying; Fakharuddin, Azhar; Schmidt-Mende, Lukas
Graphical abstract: Healing of perovskite films in nanostructures scaffolds results in improved pore-filling, formation of large grains, improved charge extraction, PV performance and also an enhanced operation stability. Highlights: Method for efficient pore filling of one-dimensional scaffolds is demonstrated. Methylamine gas environment assists in obtaining large perovskite grains. Improved charge transfer takes place upon improved pore filling. Grain size dependent device stability is demonstrated in perovskite solar cells. Abstract: High performance in perovskite solar cells is often achieved using compact metal oxide layers or their mesoporous analogues. One dimensional scaffold materials such as nanorods or nanotubes are also employed in order to improve charge collection, however, perovskite pore-filling in these nanostructures is rather low. Herein, we introduce a method to more efficiently fill the pores in two most common nanostructure architectures namely, TiO2 nanorods and nanotubes. The method employs recrystallization of perovskite films in a methylamine rich environment– the so called perovskite healing. Whereas the scanning electron microscopy imaging revealed an improved pore-filling and formation of large perovskite grains upon healing, the complementary photoluminescence and electrical characterizations revealed improved charge transfer in the healed films than their pristine rivals. We also report a notable improvement in photoconversion efficiency and a better stability under continuous light soaking in the healed perovskite films.